2017
DOI: 10.1177/0748233717699783
|View full text |Cite
|
Sign up to set email alerts
|

The toxic effects of polychlorinated biphenyl (Aroclor 1242) on Tm3 Leydig cells

Abstract: Polychlorinated biphenyls (PCBs) are ubiquitous and persistent environmental contaminants that disrupt endocrine function in biological systems, especially in the male reproductive system. Previous studies on the reproductive toxicity of PCBs have focused on the impairment of spermatogenesis, disruption of steroidogenesis, decreased sperm number, and infertility. Aroclor 1242 is a commercial mixture with an average of 42% chlorine by weight. The purpose of the present study was to elucidate the hazardous effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
(86 reference statements)
0
9
0
1
Order By: Relevance
“…Experimental in vivo studies have, however, shown that elevated exposure to PCBs disrupts and diminishes Leydig cell function in adult rats [ 44 , 45 , 46 ], and exposing lactating rats to Aroclor 1242, a PCB mixture of varying amounts of mono- through heptachlorinated homologs, caused significant adverse effects on Leydig cell function, reducing the capacity to produce T in response to LH stimulation in adult male offspring [ 47 ]. Another study of the toxic effects of Aroclor 1242 on Tm3 Leydig cells suggested that exposure to Aroclor 1242 at high concentrations may result in detrimental effects to Leydig cell homeostasis and impaired steroidogenesis, especially T biosynthesis, by inhibiting two important steroidogenic enzymes [ 48 ]. Further, PCBs are known to affect a variety of liver functions [ 49 , 50 ] and PCB-induced hepatic SHBG synthesis could therefore play a possible role contributing to the increased serum-SHBG concentrations observed.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental in vivo studies have, however, shown that elevated exposure to PCBs disrupts and diminishes Leydig cell function in adult rats [ 44 , 45 , 46 ], and exposing lactating rats to Aroclor 1242, a PCB mixture of varying amounts of mono- through heptachlorinated homologs, caused significant adverse effects on Leydig cell function, reducing the capacity to produce T in response to LH stimulation in adult male offspring [ 47 ]. Another study of the toxic effects of Aroclor 1242 on Tm3 Leydig cells suggested that exposure to Aroclor 1242 at high concentrations may result in detrimental effects to Leydig cell homeostasis and impaired steroidogenesis, especially T biosynthesis, by inhibiting two important steroidogenic enzymes [ 48 ]. Further, PCBs are known to affect a variety of liver functions [ 49 , 50 ] and PCB-induced hepatic SHBG synthesis could therefore play a possible role contributing to the increased serum-SHBG concentrations observed.…”
Section: Discussionmentioning
confidence: 99%
“…A similar kind of effect on StAR and P450 ssc mRNA expression has been noted in guinea pigs treated with fluoride and aluminium (Dong et al, 2016). Mouse Leydig cells exposed to Aroclor 1,242, a commercial mixture of PCBs, resulted in reduced Leydig cell viability and impaired testosterone biosynthesis by inhibiting two steroidogenic enzymes (3β-hydroxysteroid dehydrogenase [HSD] and 17β-HSD) (Aydin & Erkan, 2017). In adult male rats, organochlorines, namely lindane and methoxychlor, have been reported to alter the testicular levels of StAR protein, androgen-binding .…”
Section: Potential Areas Of Researchmentioning
confidence: 70%
“…Several animal studies have been conducted to examine the deleterious effects of various environmental toxicants on male fertility and decipher their possible mechanism(s) of action (Akarca-Dizakar et al, 2019;Albert, Nardelli, Lalancette, Hales, & Robaire, 2018;Aydin & Erkan, 2017;Campos et al, 2019;Kim, Cheon, Choi, & Lee, 2019;Kolatorova et al, 2018). The focus of this review is to shed light on the impact of environmental contaminants on male reproduction and the underlying mechanism of action based on the recent scientific data available.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Um dos principais mecanismos de ação dos PCBs é a indução de estresse oxidativo (ALY,H. A. et al, 2017;ALY, H. A.;ABDEL-NAIM, 2009;AYDIN; ERKAN, 2017).…”
unclassified